2009
DOI: 10.1127/0935-1221/2009/0021-1935
|View full text |Cite
|
Sign up to set email alerts
|

Water contents of pyroxenes in intraplate lithospheric mantle

Abstract: Water contents of clinopyroxene and orthopyroxene in mantle peridotites from various xenolith occurrences in intraplate settings (both oceanic and continental) were determined by Fourier Transform Infrared Spectroscopy (FTIR). The localities are as follow: Sal Island (Cape Verde Archipelago); Baker Rocks and Greene Point (Northern Victoria Land, Antarctica); Panshishan and Lianshan (Subei Basin, Eastern China). They represent well-known localities where detailed petrographical and geochemical studies have alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 61 publications
9
65
0
1
Order By: Relevance
“…Rare opx grains have a band at 3100 cm − 1 . The positions of the absorption bands are similar to those reported in previous studies on both natural and experimental minerals and interpreted as the vibration of structural OH (Skogby and Rossman, 1989;Skogby et al, 1990;Bell and Rossman, 1992;Ingrin and Skogby, 2000;Peslier et al, 2002;Grant et al, 2007;Li et al, 2008;Yang et al, 2008;Bonadiman et al, 2009;Gose et al, 2009;Green et al, 2010;Xia et al, 2010;Hao et al, 2011;Sundvall and Stalder, 2011). The relative absorbance of these bands varies among grains in a given sample due to variable orientation of grains with respect to the IR beam direction.…”
Section: Hydrogen Speciation and H 2 O Contentssupporting
confidence: 66%
See 2 more Smart Citations
“…Rare opx grains have a band at 3100 cm − 1 . The positions of the absorption bands are similar to those reported in previous studies on both natural and experimental minerals and interpreted as the vibration of structural OH (Skogby and Rossman, 1989;Skogby et al, 1990;Bell and Rossman, 1992;Ingrin and Skogby, 2000;Peslier et al, 2002;Grant et al, 2007;Li et al, 2008;Yang et al, 2008;Bonadiman et al, 2009;Gose et al, 2009;Green et al, 2010;Xia et al, 2010;Hao et al, 2011;Sundvall and Stalder, 2011). The relative absorbance of these bands varies among grains in a given sample due to variable orientation of grains with respect to the IR beam direction.…”
Section: Hydrogen Speciation and H 2 O Contentssupporting
confidence: 66%
“…The water content of ol from spinel peridotite xenoliths hosted by alkaline basalts is typically lower than 10 ppm, possibly due to low initial water contents and/or diffusive H-loss during xenolith ascent to the surface (e.g., Demouchy et al, 2006;Peslier and Luhr, 2006). In contrast, pyroxenes coexisting with olivine appear to retain their initial H contents to a much larger extent (Peslier et al, 2002;Bell et al, 2004;Grant et al, 2007;Yang et al, 2008;Bonadiman et al, 2009;Gose et al, 2009;Xia et al, 2010;Sundvall and Stalder, 2011). In our study, the OH contents measured in ol (~0 ppm) are unlikely to represent their source value; the latter can be recalculated for ol by H 2 O partition between pyroxene and olivine.…”
Section: Hydrogen Speciation and H 2 O Contentsmentioning
confidence: 90%
See 1 more Smart Citation
“…Laboratory experiments demonstrate that the difference of hydrogen diffusivities between olivine and pyroxene (Ingrin Histograms of water contents in NAMs from craton, off-craton, oceanic lithosphere, mantle wedge and lava. References: craton (Skogby et al, 1990;Rossman, 1992a, 1992b;Kurosawa et al, 1997;Matsyuk et al, 1998;Bell and Ihinger, 2000;Bell et al, 2004b;Matsyuk and Langer, 2004;Mosenfelder et al, 2006a;Grant et al, 2007;Matveev and Stachel, 2007;Li et al, 2008;Peslier et al, 2008Peslier et al, , 2010Peslier et al, , 2012Yang et al, 2008;Bonadiman et al, 2009;Xia et al, 2010Xia et al, , 2013aSundvall and Stalder, 2011;Baptiste et al, 2012;Hao et al, 2012;Doucet et al, 2014;Li et al, 2015;Pintér et al, 2015); off-craton Rossman, 1992a, 1992b;Yu et al, 2011;Hao et al, 2014); oceanic lithosphere (Bonadiman et al, 2009;Bizimis and Peslier, 2015;Demouchy et al, 2015); mantle wedge (Kurosawa et al, 1997;Peslier et al, 2002;Peslier and Luhr, 2006); phenocrysts from lava (Skogby et al, 1990;Bell and Rossman, 1992b;Jamtveit et al, 2001;Matsyuk and Langer, 2004;Matveev et al, 2005;Koch-Müller et al, 2006;…”
Section: Intra-mineral Water Distributionmentioning
confidence: 97%
“…There are a considerable number of studies on the water content in NAMs of mantle xenoliths from different cratons, including Kaapvaal craton (e.g., Peslier et al, 2010Peslier et al, , 2012Baptiste et al, 2012), Siberian craton (e.g., Matsyuk and Langer, 2004;Doucet et al, 2014), Tanzanian craton (e.g., Baptiste et al, 2012;Hui et al, 2015), Colorado plateau (e.g., Li et al, 2008), and NCC (e.g., Yang et al, 2008;Bonadiman et al, 2009;Xia et al, 2010Xia et al, , 2013a. Previous studies have shown that NCC has lost its ancient lithospheric mantle root (e.g., Fan et al, 2000).…”
Section: Hydrolytic Weakening and Craton Stabilitymentioning
confidence: 99%